CORRELATION BETWEEN PLASMATIC VITAMIN D LEVEL AND REFRACTIVE STATUS IN CHILDREN WITH DISABILITIES - Larisa Bianca Holhoș; Teodora-Laura Holhoș; Mihaela Cristiana Coroi; Carina Petricău; Liviu Lazăr (Amaltea Medical Publishing House, 2021)
Introduction. Literature confirms that refractive errors are the most common, easily corrected, eye morbidity in children with disabilities. Early intervention such as wearing eyeglasses can positively impact the lives of these children. The implication of vitamin D status is investigated as a possible proactive measure in eye conditions. Aim. The current study proposed to asses the refractive status as well as vitamin D plasmatic level in 161 children. Another aim was to investigate whether myopia corelates with a lower plasmatic vitamin D level. Methods. A retrospective case-control study was done on 161 children, divided into two groups: the study group (children with disabilities) and the contol group (children without disabilities). The age range of children included in the study was from 5 to 16 years old. Results. Refractive errors were found to be more frequent in the group of children with disabilities and of these, astigmatism was the most frequent refractive disorder identified. Also, the plasmatic vitamin D level was found to be lower in those with myopia reguardless of disability status. Conclusions. Children with disabilities are diagnosed with refractive errors twice more frequenty than their healthy peers. Parents, medical staff and teachers should be aware of this risk factor and be more attentive because the presence of uncorrected refractive disorders may not be visible in most children, especially those with special needs.